2014
DOI: 10.1177/0885328214551373
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma encapsulation in hyaluronic acid/gelatin-BCP hydrogel for growth factor delivery in BCP sponge scaffold for bone regeneration

Abstract: Microporous calcium phosphate based synthetic bone substitutes are used for bone defect healing. Different growth factor loading has been investigated for enhanced bone regeneration. The platelet is a cellular component of blood which naturally contains a pool of necessary growth factors that mediate initiation, continuation, and completion of cellular mechanism of healing. In this work, we have investigated the encapsulation and immobilization of platelet-rich plasma (PRP) with natural polymers like hyaluroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…At the same seeding density, there were more viable cells in HA-CPN/PRP/BCP than in HA-CPN with significant difference found throughout the culture period ( p < 0.05), which indicates HA-CPN/PRP/BCP provided a better environment for rASCs proliferation than HA-CPN. This result is consistent with a previous report showing HA/gelatin/PRP hydrogel loaded in BCP scaffolds could enhance proliferation rate of MC3T3-E1 pre-osteoblast cells [ 43 ]. We also reported that incorporation of BCP into HA-CPN could significantly raise the cell proliferation rate of human fetal osteoblastic cells due to the beneficial effects of BCP [ 44 ].…”
Section: Resultssupporting
confidence: 94%
“…At the same seeding density, there were more viable cells in HA-CPN/PRP/BCP than in HA-CPN with significant difference found throughout the culture period ( p < 0.05), which indicates HA-CPN/PRP/BCP provided a better environment for rASCs proliferation than HA-CPN. This result is consistent with a previous report showing HA/gelatin/PRP hydrogel loaded in BCP scaffolds could enhance proliferation rate of MC3T3-E1 pre-osteoblast cells [ 43 ]. We also reported that incorporation of BCP into HA-CPN could significantly raise the cell proliferation rate of human fetal osteoblastic cells due to the beneficial effects of BCP [ 44 ].…”
Section: Resultssupporting
confidence: 94%
“…For example, chitosan scaffolds were proposed for PRP encapsulation and growth factor controlled release [12]. Similarly, PRP loaded scaffolds of hyaluronic acid/gelatin or gelatin were investigated for bone healing [3,26]; the same clinical application was proposed for PRP loaded collagen scaffolds [27], while gelatin hydrogels were developed for meniscal regeneration [28]. Although these approaches alleviate growth factors burst release and unfavorable mechanical properties of PRP, they are based on the use of preformed scaffolds, which imply surgical administration.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) contains a cocktail of multiple growth factors, including platelet derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor (TGF-β1), basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), and insulin-like growth factor [ 16 , 17 , 18 ], and is frequently used in soft and bone tissue engineering [ 19 , 20 , 21 , 22 ]. Studies have shown that these growth factors strongly contribute to cell-extracellular matrix communication during regenerative activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%